2015
DOI: 10.1021/acs.inorgchem.5b00013
|View full text |Cite
|
Sign up to set email alerts
|

New Three-Fold Interpenetrated Uranyl Organic Framework Constructed by Terephthalic Acid and Imidazole Derivative

Abstract: A new 3-fold interpenetrated uranyl organic framework, UO2(bdc)(dmpi), was hydrothermally synthesized using 1,4-benzenedicarboxylic acid (H2bdc) and 1-(4-(1H-imidazol-1-yl)-2,5-dimethylphenyl)-1H-imidazole (dmpi). This framework, which was determined by synchrotron radiation X-ray, exhibited a new 3-fold interpenetrated (2,4)-connected topology with the Schläfli symbol of (12(6))(12)2. Additionally, large incurvation happened to the bond angle of [O=U=O](2+), which was always arranged in a rigorous line. Compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Recently,o ur group reported ar are case of an onlinear[ O =U=O] bond with ab ond angle of 173.3(5)8 in au ranyl complex with terephthalica cid and bis-imidazole ligands. [20] Here, the bond angle of 172.0(9)8 represents am ore significant bending of the [O=U=O] bond, which might result in al arger extent of inert U=Oa ctivation. [21] The unique trinuclearu ranyl units in at ridentate mode offer a2 Dp olyrotaxane network, whereas the sulfate ion-bridged uranyl dimers extendi nto a1 Dp olyrotaxanec hain in compound 1.These two isolated supramolecular polyrotaxane moi-eties can further interact with each other,w here different layers of 2D polyrotaxane networks are threaded in an ordered array of 1D polyrotaxane chains (Figures 4a-d andS 8i nt he Supporting Information).…”
Section: Synthesis and Crystallographic Analysis Of Compoundmentioning
confidence: 99%
“…Recently,o ur group reported ar are case of an onlinear[ O =U=O] bond with ab ond angle of 173.3(5)8 in au ranyl complex with terephthalica cid and bis-imidazole ligands. [20] Here, the bond angle of 172.0(9)8 represents am ore significant bending of the [O=U=O] bond, which might result in al arger extent of inert U=Oa ctivation. [21] The unique trinuclearu ranyl units in at ridentate mode offer a2 Dp olyrotaxane network, whereas the sulfate ion-bridged uranyl dimers extendi nto a1 Dp olyrotaxanec hain in compound 1.These two isolated supramolecular polyrotaxane moi-eties can further interact with each other,w here different layers of 2D polyrotaxane networks are threaded in an ordered array of 1D polyrotaxane chains (Figures 4a-d andS 8i nt he Supporting Information).…”
Section: Synthesis and Crystallographic Analysis Of Compoundmentioning
confidence: 99%
“…4,5 Although our studies of complexes of cis-1,2-cyclohexanedicarboxylate have to date been limited, they do indicate significant differences to be associated with this isomeric form, providing reason for an extension to examination of the complexes of cis-and trans-1,4-cyclohexanedicarboxylic acid, for which but a single uranyl molecular complex of the trans isomer is known. 6 This acid is the alicyclic counterpart of terephthalic acid, which has been used in the synthesis of several coordination polymers, [7][8][9][10][11][12][13][14][15][16][17][18][19] most often one-or two-dimensional (1D or 2D), with only two cases of threedimensional (3D) frameworks, 12,16 and also some examples of interpenetrated nets. 8,14,19 Some of these complexes are heterometallic, 7,11,13,18 and display photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…6 This acid is the alicyclic counterpart of terephthalic acid, which has been used in the synthesis of several coordination polymers, [7][8][9][10][11][12][13][14][15][16][17][18][19] most often one-or two-dimensional (1D or 2D), with only two cases of threedimensional (3D) frameworks, 12,16 and also some examples of interpenetrated nets. 8,14,19 Some of these complexes are heterometallic, 7,11,13,18 and display photocatalytic activity. 7,13,18 We used two commercially available forms of 1,4-cyclohexanedicarboxylic acid, the pure trans form (t-1,4-chdcH2), which, when the two acid groups are in equatorial position, is geometrically close to terephthalic acid, and a mixture of cis and trans isomers (c,t-1,4-chdcH2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,9] In metallasupramolecular chemistry, although the pyridine-based ligands have been widely used as rigid neutral bridging linkers, the use of the imidazole-based linkers is still limited. Jin, [10] Mukherjee [11] and others [12] have reported several imidazole-based bridging ligands which are similar to pyridine-based ligands. They have also demonstrated that the imidazole-derivatives can bind metal ions much stronger than pyridyl linkers.…”
Section: Introductionmentioning
confidence: 96%